2022
DOI: 10.3389/fonc.2022.904464
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pyroptosis-Related Gene Signature for Predicting the Prognosis and the Associated Immune Infiltration in Colon Adenocarcinoma

Abstract: BackgroundPyroptosis has been demonstrated to be an inflammatory form of programmed cell death recently. However, the expression of pyroptosis-related genes (PRGs) in colon adenocarcinoma (COAD) and their correlations with prognosis remain unclear.MethodsData of COAD patients were obtained from The Cancer Genome Atlas (TCGA) database to screen differentially expressed genes (DEGs). Univariate Cox regression analysis and the LASSO Cox regression analysis were applied to construct a gene signature. All COAD pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Among them, Chen et al. ( 68 ) performed the analysis based on the samples in TCGA, and the GEO data set was the validation set. Compared to this study, our research differs significantly in three main aspects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, Chen et al. ( 68 ) performed the analysis based on the samples in TCGA, and the GEO data set was the validation set. Compared to this study, our research differs significantly in three main aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis, a type of programmed cell death characterized by an inflammatory response, can significantly influence the TIME and thus regulate the development and prognosis of malignancy (67). Although some relevant studies have been reported (12,43,68), the exploration of prognostic models based on PRGs in CC remains necessary and valuable. Among them, Chen et al (68) performed the analysis based on the samples in TCGA, and the GEO data set was the validation set.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A report indicated that succinate dehydrogenases (SDHs) are closely related to mitochondria and are primarily involved in the occurrence and progression of tumors ( 12 , 13 ). Moreover, succinate, which accumulates as a result of SDH inhibition, inhibits HIF-α prolyl hydroxylases in the cytosol, stabilizes and activates Hypoxia-inducible factor-1 (HIF-1) ( 14 ).…”
Section: Introductionmentioning
confidence: 99%